OPTIMALISASI MANAJEMEN PROYEK BERBASIS WEB DENGAN REDMINE DAN SVN PADA PEMBUATAN WEBSITE - Anik Andriani (Paradigma, 2012)
Website increasingly popular and is used in almost all fields. This is because the use of a website to support the ease of dissemination of information. Website development is done in a project team often encounter obstacles and barriers in both web development and oversight of development, especially when the team is in the distance and the lack of face to face meetings between team members in the development of the website. Redmine is a web-based projectmanagement application that can be applied in the creation of websites. With support Subversion(SVN) to manage project documents, redmine a web-based project management tool that can be relied upon. The method used in study is experimental. This study aimed to implement a web-based project management application using redmine and SVN to facilitate the creation, development and management of the website. The result is a website creation project withredmine and SVN to facilitate the creation, development, and management of the website. The result is a website creation project with redmine and SVN can reduce the barriers and constraints of the project of the website although the project team members are in different locations and without face-to-face. In addition, by using redmine and SVN maintenance and control of thecompany’s website also easier.Keywords: website, web-based project management, redmine, svn